Odors Associated With Autobiographical Memory Induce Visual Imagination of Emotional Scenes as Well as Orbitofrontal-Fusiform Activation - Masaoka, Yuri; Sugiyama, Haruko; Yoshida, Masaki; Yoshikawa, Akira; Honma, Motoyasu; Koiwa, Nobuyoshi; Kamijo, Shotaro; Watanabe, Keiko; Kubota, Satomi; Iizuka, Natsuko; Ida, Masahiro; Ono, Kenjiro; et al. (Frontiers in Neuroscience, 2021)
Specific odors can induce memories of the past, especially those associated with autobiographical and episodic memory. Odors associated with autobiographical memories have been found to elicit stronger activation in the orbitofrontal cortex, hippocampus, and parahippocampus compared with odors not linked to personal memories. Here, we examined whether continuous odor stimuli associated with autobiographical memories could activate the above olfactory areas in older adults and speculated regarding whether this odor stimulation could have a protective effect against age-related cognitive decline. Specifically, we used functional magnetic resonance imaging to investigate the relationship between blood oxygen levels in olfactory regions and odor-induced subjective memory retrieval and emotions associated with autobiographical memory in older adults. In our group of healthy older adults, the tested odors induced autobiographical memories that were accompanied by increasing levels of retrieval and the feeling of being ‘brought back in time’. The strength of the subjective feelings, including vividness of the memory and degree of comfort, impacted activation of the left fusiform gyrus and left posterior orbitofrontal cortex. Further, our path model suggested that the strength of memory retrieval and of the emotions induced by odor-evoked autobiographical memories directly influenced neural changes in the left fusiform gyrus, and impacted left posterior orbitofrontal cortex activation through the left fusiform response.